Axis spinous process malformations are commonly identified in a sample of English Bull Terriers without associated clinical signs. Issue 5 (14th May 2021) - Frias, João Miguel; De Decker, Steven; Dirrig, Helen; Fenn, Joe
Abstract: Congenital cervical vertebral malformations (CCVM) have been infrequently reported in veterinary medicine, with limited examples of axis spinous process malformations. The objective of this retrospective cross‐sectional study was to describe the radiological characteristics, prevalence, and clinical relevance of a characteristic axis vertebral malformation in a sample of English Bull Terriers (EBTs). Medical records and diagnostic imaging studies of the cervical vertebral column of EBTs presenting for any reason were reviewed and described. Based on evaluation of the images, EBTs were divided in two groups; axis spinous process malformation and normal cases. Referring veterinary surgeons were contacted for long‐term follow‐up information. A total of 27 cervical radiographs, 23 CT, and nine MRI studies from 53 EBTs were reviewed. An axis spinous process malformation, characterized by a linear defect of varying length along the base of the spinous process, was identified in 22 of 53 EBTs (41.5%). There was no significant difference in age, body weight, or sex ( P  < .05) between EBTs with and without the malformation. No traumatic causes or clinical signs were identified in EBTs with the malformation that could be directly attributed to it. To the authors' knowledge, this is the first report of a malformation of the axis spinous process in a sample of EBTs. The malformation was not associated with clinical signs and should not be misinterpreted as a traumatic vertebral fracture or other pathology.